La vida buena del evangelio: Carta pastoral del Arzobispo Metropolitano de San Juan, Puerto Rico - González Nieves, Roberto Octavio (My University, 2016)
Carta pastoral del Arzobispo Metropolitano de San Juan, Puerto Rico
Keywords: Evangelio.; Bible.; González Nieves, Roberto Octavio.; Catholic Church--Pastoral letters and changes.